2020
DOI: 10.1111/ajps.12526
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting for Confounding with Text Matching

Abstract: We identify situations in which conditioning on text can address confounding in observational studies. We argue that a matching approach is particularly well-suited to this task, but existing matching methods are ill-equipped to handle high-dimensional text data. Our proposed solution is to estimate a low-dimensional summary of the text and condition on this summary via matching. We propose a method of text matching, topical inverse regression matching, that allows the analyst to match both on the topical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…STM-based representations appear somewhat more sensitive to tuning parameters, with representations that include a large number of estimated topics achieving higher average match quality than those constructed with fewer topics. This result provides further support for the findings in Roberts, Stewart, and Nielsen (2019), where the authors found that matching on more topics generally led to better results in terms of recovering pairs of nearly identical documents.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…STM-based representations appear somewhat more sensitive to tuning parameters, with representations that include a large number of estimated topics achieving higher average match quality than those constructed with fewer topics. This result provides further support for the findings in Roberts, Stewart, and Nielsen (2019), where the authors found that matching on more topics generally led to better results in terms of recovering pairs of nearly identical documents.…”
Section: Resultssupporting
confidence: 86%
“…Text matching is widely applicable in the social sciences. Roberts, Stewart, and Nielsen (2019) show how text matching can produce causal estimates in applications such as international religious conflict, government-backed internet censorship, and gender bias in academic publishing. We believe that the framework presented in this paper will help expand the scope and usability of text matching even further and will facilitate investigation of text data across a wide variety of disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations